2010
DOI: 10.4067/s0718-95162010000200010
|View full text |Cite
|
Sign up to set email alerts
|

ANTIOXIDANT COMPOUNDS IN SKIN AND PULP OF FRUITS CHANGE AMONG GENOTYPES AND MATURITY STAGES IN HIGHBUSH BLUEBERRY (Vaccinium corymbosum L.) GROWN IN SOUTHERN CHILE

Abstract: We evaluated the genotype and maturity effects on antioxidant activity and phenolic compounds of whole, skin and pulp fruits from three highbush blueberry cultivars (cv. Brigitta, cv. Bluegold and cv. Legacy) grown in southern Chile. Total antioxidant activity (TAA) in ripe fruits varied among the cultivars in the order Legacy > Brigitta > Bluegold. We found that TAA in unripe green and fully ripe fruits was high and similar between them, whereas the lowest levels were found in intermediate ripe fruits. The sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
61
4
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(80 citation statements)
references
References 54 publications
9
61
4
3
Order By: Relevance
“…The ORAC values observed in control fruits were higher than those reported by Ehlenfeldt and Prior (2001) for Brigitta (17.7 µmol TE g -1 FW) and Legacy (13.5 µmol TE g -1 FW), which were similar to those reached in fruits from plants treated with 800 mg L -1 . This result was consistent with that reported by Ribera et al (2010), indicating that highbush blueberry fruits grown in southern Chile have exceptionally higher antioxidant activity in comparison to those cultivated in the Northern Hemisphere. The DPPH methodology used to determine antioxidant activity indicated a C×B (P≤ 0.05; Table 2), which increases the activity in Legacy fruits treated with 200 and 400 mg L -1 compared to the control (P≤0.05; Figure 4).…”
Section: Resultssupporting
confidence: 83%
“…The ORAC values observed in control fruits were higher than those reported by Ehlenfeldt and Prior (2001) for Brigitta (17.7 µmol TE g -1 FW) and Legacy (13.5 µmol TE g -1 FW), which were similar to those reached in fruits from plants treated with 800 mg L -1 . This result was consistent with that reported by Ribera et al (2010), indicating that highbush blueberry fruits grown in southern Chile have exceptionally higher antioxidant activity in comparison to those cultivated in the Northern Hemisphere. The DPPH methodology used to determine antioxidant activity indicated a C×B (P≤ 0.05; Table 2), which increases the activity in Legacy fruits treated with 200 and 400 mg L -1 compared to the control (P≤0.05; Figure 4).…”
Section: Resultssupporting
confidence: 83%
“…In this study, the effects of different short-term N treatments on the chemical, physiological and biochemical characteristics of highbush blueberry were evaluated. It is widely reported that leaves and fruits of blueberry exhibit a particularly high content of phenolic compounds (Ribera et al, 2010), which could be affected by the short-term N supply as previously found for other plants, such as Arabidopsis and chamomile (Kováčik et al, 2007;Olsen et al, 2008).…”
Section: Resultsmentioning
confidence: 99%
“…Since 1985, the highbush blueberry (Vaccinium corymbosum L.) has become an important crop cultivated in Chile (Lyrene and Muñoz, 1997;Ribera et al, 2010). Nonetheless, information concerning the physiology of this crop beyond its beneficial effects is lacking.…”
Section: Research Papermentioning
confidence: 99%
“…A linear relationship was observed between total phenolics and FRAP values for blueberries (Koca and Karadeniz, 2009). Anthocyanin compounds are mainly concentrated in the skin of berries (Ribera et al, 2010).…”
Section: Resultsmentioning
confidence: 99%